Analisis Metode Belajar Mahasiswa BIPA Universitas PGRI Adi Buana Surabaya - Mayada Mayada; Resdianto Permata Raharjo; Eko Hardinanto; Arisni Kholifatu Amalia Shofiani; Ahmad Faiz (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
Learning Indonesian for Foreign Speakers (BIPA) poses unique challenges, particularly in understanding Indonesia's linguistic and cultural distinctiveness. Foreign students at Universitas PGRI Adi Buana Surabaya come from diverse countries of origin, which naturally influences their preferences in absorbing lecture materials. This study aims to identify and analyze the learning methods applied by BIPA students at Universitas PGRI Adi Buana Surabaya and the factors influencing them. This study utilized a descriptive qualitative approach. Data were collected through classroom observation, in-depth interviews with BIPA students, and open-ended questionnaires. Data analysis was conducted using data reduction, data display, and conclusion-drawing techniques. The results of the study indicate that BIPA students at Universitas PGRI Adi Buana Surabaya tend to combine a communicative approach with cultural immersion. Out-of-class activities, such as direct interaction with native speakers within the campus environment and the utilization of audiovisual-based digital media, proved to be the most effective methods for them. Personal motivation factors and social-cultural adaptation in Surabaya play an important role in the selection of these methods.